Ecological factors associated with pest status in Callosobruchus (Coleoptera: Bruchidae): High host specificity of non-pests to Cajaninae (Fabaceae) - Tuda M. (2014)
Larval host plants of six Callosobruchus species (Coleoptera: Bruchidae), including pest species, were discovered by collecting the seeds of wild (or inedible) and cultivated edible legumes in the field in Taiwan, Thailand, continental China, Myanmar, Nepal and the Philippines. A close relationship between Asian Callosobruchus species and the leguminous subtribe Cajaninae was revealed: Rhynchosia species were commonly used by three Callosobruchus species, wild and cultivated species of Cajanus and two Dunbaria species, respectively, by single species. Two Taiwanese species were confirmed to be conspecific with continental species. We further reviewed host legumes of 11 species of Callosobruchus including nine species of pests. There were significant positive correlations between geographic distribution range and host range at all three taxonomic levels of hosts. Principal component analysis on geographic distribution range, host range, altitude of distribution, utilizations of cultivated hosts, of Cajaninae and of Phaseolinae showed that the first axis (PC1) described 52% of total variance, which was related significantly with the frequencies of utilization of cultivated legumes (0.93), and of Cajaninae (Cajanus, Dunbaria and Rhynchosia) (-0.85). PC1 was also positively correlated with the frequency of utilization of Phaseolinae (Vigna and Lablab) (0.68), geographical range (0.67) and with host range (0.67) before Bonferroni corrections. Contrary to the polyphagy of the widely distributed pest Callosobruchus, non-pest species exhibited fidelity to single specific genera of wild or inedible legumes, and pests with limited distribution are specific to leguminous subtribes. Non-pests are characterized by tight association with Cajaninae. We concluded that specialization to non-economic Cajaninae prevents a species of Callosobruchus from becoming a pest of cultivated legumes. © 2004 Elsevier Ltd. All rights reserved.